PERANAN KERTA DESA DALAM PENYELESAIAN SENGKETA PERCERAIAN DI DESA ADAT GULINGAN KAB BADUNG - Yulianti, Ni Putu Nita; Udytama, I Wayan Wahyu Wira (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
This research explores the role of Kerta Desa (Village Council) in resolving divorce cases in Gulingan Customary Village, Bali. It provides insights into the role of Kerta Desa in resolving divorce cases in Bali, highlighting the implementation of customary law and social dynamics in the context of family law. The issues addressed in this research are the roles of Kerta Desa in resolving divorce disputes in Gulingan Customary Village, Badung Regency, as well as the challenges faced by Kerta Desa in resolving divorce disputes in Gulingan Customary Village, Badung Regency. The methodology employed in this research is empirical legal research. The conclusion drawn from this research is that Gulingan Customary Village applies customary law based on the concept of Tri Hita Karana, where divorce resolution also involves the Klian Adat (Customary Leaders) in each Banjar Adat (Customary Neighborhood), who engage in mediation, negotiation, and conciliation. Divorce rulings are based on the principle of joint ownership (druwenang sareng-sareng) for property, child custody, and post-divorce obligations. In resolving divorce disputes, Kerta Desa Adat Gulingan faces internal challenges related to the mechanisms and procedures for handling customary cases. The village does not yet have specific regulations for divorce, prioritizing peace based on the principle of druwenang sareng-sareng.